Editing Experiment: The New Modernist Editing and Dorothy Richardson's Pilgrimage. Issue 1 (February 2020) - Guy, Adam; McCracken, Scott
Abstract : This article examines the challenges experimental writing poses for textual editing, drawing on the experience of the Dorothy Richardson Editions Project, which was inaugurated in 2007 with the aim of producing new scholarly editions of Richardson's fiction and letters. Here we focus on Richardson's thirteen-volume novel sequence Pilgrimage (1915–67) and the particular problems its constantly unfolding experimental aesthetic present for both the critic and the scholarly editor. We adopt Adorno's concept of 'constructive methods' to describe Richardson's project, the composition of a narrative without a predictable endpoint, asking what kind of editorial practice best captures her unconventional and deliberately inconsistent approach to writing. We conclude by discussing the implications that editing Pilgrimage might have for a broader understanding of modernist aesthetics.